Hubungan Frekuensi Kunjungan Antenatal Care (ANC) dengan Kejadian Prematur - Evi Esti Utami; Susi Ernawati; Winda Irwanti (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2014)
The cause of infant mortality is mostly due to perinatal matters. Almost 2-27% of all perinatal death is caused by prematurity with low birth weight (BBLR). Reducing mortality rate on perinatal can be achieved by observing all pregnant women and ﬁ nding as well as addressing inﬂ uenced factors of neonatal safety. This research aims to identify correlation between frequencies of Antenatal Care (ANC) with incidence of prematurity. This is an observational study with case-control design using retrospective approach. Total population was 1335 and of 156 was choosen as research respondents deviding into 78 as case respondents and 78 as control groups. The result of statistic analysis showed that p value=0,837 (p>0,05) means frequencies of ANC did not have correlation with prematurity. Conclusion, (1) during the period of 1 January 2011 and 29 February 2012, it found 207 (8,13%) premature baby delivered, (2) at about 80,8% mother who delivered premature baby had normal ANC 4 times or more with the pattern 1-1-2 in every semester, (3) statistically ANC was not having correlation with premature baby.